The return of the real : the avant-garde at the end of the century - Foster, Hal. (Cambridge, Mass. : MIT Press, 1996)
- Who's afraid of the neo-avant-garde? ##- The crux of minimalism ##- The passion of the sign ##- The art of cynical reason ##- The return of the real ##- The artist as ethnographer ##- Whatever happened to postmodernism?
"An October book."
Includes bibliographical references (p. [227]-292) and index.
boek